A review on economically-feasible and environmental-friendly technologies promising a sustainable environment - Prangya Rath (Elsevier, 2021)
In recent years, there has been an alarming increase in global problems such as pollution levels, global warming, and climatic changes. Studies have highlighted that these problems have not only intervened and contaminated abiotic resources but also biotic resources. These have become a serious threat and generated many environment related concerns. It has harmed the health of humans, animals, and plants. It has led to an increase of many diseases, brought down the life expectancy, and affected crops and agricultural pattern. This scenario has led to increase in awareness and has compelled various organizations to come together in mitigating the problem. Achieving sustainable development goals to protect and sustain environment has become an utmost need. Great efforts and expenditures are being made to provide various eco-friendly technologies for tackling and mitigating the problem. However, not all technologies are successful for practical implementation. Some criteria which play a decisive role include their working principle, effectiveness, carbon sequestration capabilities, cost management and sustainable outcomes. The review focuses on highlighting some of such technologies which fulfils all the above criteria. These innovations have been analysed for their mode of action, ability to reduce carbon footprint level, combat air pollutants, cost effectiveness or economic angle, and future aspects. They assure that no hazardous by-products are generated, and ultimately results in a low-cost alternative approach for appropriate applications. Their application on a wider scale would be meet SDGs. As a result, they have a promising future keeping in mind both green sustainability and economic sustainability. The review will be beneficial for gaining insight into present techniques, analysing modifications required, determining new approaches, and further broaden the aspects for research development.